2004
DOI: 10.1590/s1806-37132004000400006
|View full text |Cite
|
Sign up to set email alerts
|

Óbitos atribuídos à tuberculose no Estado do Rio de Janeiro

Abstract: INTRODUÇÃO:Em 1998, o Rio de Janeiro era o estado de maior incidência e mortalidade por tuberculose do Brasil. O Sistema de Informação de Agravos de Notificação em Tuberculose (SINAN-TB-RJ) não era confiável. OBJETIVO: Utilizar o estudo dos óbitos por tuberculose como instrumento de avaliação do programa de controle de tuberculose. MÉTODO: Foram realizados estudos descritivos do SINAN-TB-RJ e do Sistema de Informação de Mortalidade em tuberculose do Rio de Janeiro (SIM-TB-RJ) e os dois bancos de dados foram cr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
40
1
22

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(75 citation statements)
references
References 8 publications
12
40
1
22
Order By: Relevance
“…Another study, carried out in Brazil, in the state of Rio de Janeiro, (16) reported a median of time from the onset of symptoms up to diagnosis, for the population in general, of 60 days, which can indicate problems of access to health care facilities similar to those that were found in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…Another study, carried out in Brazil, in the state of Rio de Janeiro, (16) reported a median of time from the onset of symptoms up to diagnosis, for the population in general, of 60 days, which can indicate problems of access to health care facilities similar to those that were found in the present study.…”
Section: Discussionsupporting
confidence: 75%
“…The high incidence of pulmonary TB found in this study was expected, as the pulmonary system is the most manifestation site of this disease (6,13,19) . The clinical assessment and the diagnostic tests employed are the most common and least expensive techniques to identify pulmonary TB (20)(21) .…”
Section: Discussionsupporting
confidence: 59%
“…Initially, many deaths were observed with PTB as the basic cause, without any mention of bacteriological or histological confirmation, similar to studies undertaken in Campo Grande, State of Mato Grosso do Sul (45) and in the State of Rio de Janeiro (46) . This result identifi es a critical area that health services need to investigate in view of the possibility of false positives.…”
Section: Discussionsupporting
confidence: 61%